The Effect of Work Culture, Work Motivation, and Work Stress on Employee Performance at Royal Prima Hospital Medan - Indah Lestari Simanjuntak; Muhammad Agung Anggoro; Wansena Purba; Brigita Sinabang; Munawarah Munawarah (SEAN Institute, 2026)
This study examines the effect of work culture, work motivation, and work stress on employee performance at Royal Prima Hospital Medan. The background of this study is based on the important role of human resources in supporting the quality of hospital services, particularly among non-medical employees who still face various challenges, such as lack of discipline, work delays, and relatively high work pressure. This study employed a quantitative approach, with data collected through questionnaire distribution. The research population consisted of 150 employees, and the sampling technique used was saturated sampling; therefore, the entire population was included as respondents. Data were analyzed using multiple linear regression with the assistance of statistical software. The results show that, partially, work culture has a positive and significant effect on employee performance, with a significance value of 0.034. Work motivation also has a positive and significant effect, with a significance value of 0.005. Meanwhile, work stress has a positive and significant effect, with a significance value of 0.000, and is identified as the most dominant variable. Simultaneously, the three independent variables have a significant effect on employee performance, as indicated by an F-count value of 84.627 and a significance level of 0.000. The coefficient of determination (R²) value of 0.635 indicates that 63.5% of the variation in employee performance can be explained by work culture, work motivation, and work stress, while the remaining percentage is influenced by other factors outside this study. Therefore, it can be concluded that these three variables play an important role in improving employee performance at Royal Prima Hospital Medan.